(untitled) (Praxis Educativa, 2012)
A “Move” programme was proposed in order to increase public officials’ phy-sical activity level and to know their opi-nions about the active break programme. 15 - minute active breaks were carried out twice a week, for 4 months at their workplace. The International Physical Activity Questionnaire (IPAQ) and another test designed by ourselves were administered to all participants to assess the active break programme. Results revealed that there was a significant difference after intervention, increasing physical activity level (t = -1.391, with 95% of reliance level). Participants who initially classified as Low PA level, showed a decrease from 68.9% to 59%; those classified as Mo-derate PA showed a decrease from 18.3% to 16.9%, and those classified as High PA level increased from 17.8% to 24%. In addition, the active break programme was highly valued, obtaining more than a 90% acceptance from public officials.